Layered titanium-based composite material with alternate soft and hard layers and preparation method of layered titanium-based composite material
By using laser technology to build a layered structure with soft and hard layers on the surface of the titanium alloy matrix, the problems of low strength and high cost of interface bonding of metal matrix composite materials are solved, and the high strength, wear resistance and corrosion resistance of the material are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411643200.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
Existing metal-based composite materials have problems of low interface bonding strength and high cost.
Laser cleaning, laser cladding and laser nitriding technologies are used to build a layered structure with soft and hard layers on the surface of the titanium alloy substrate, forming alternating TC4 soft layers and TiN hard layers.
It significantly improves the comprehensive mechanical properties of the material, including wear resistance, impact resistance and corrosion resistance, reduces production costs, and improves the service life of the material.
Smart Images

Figure CN119506769A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to but is not limited to the technical field of metal-based composite materials, and in particular relates to a layered titanium-based composite material with alternating soft and hard layers and a preparation method thereof. Background Art
[0002] Metal matrix composites are new composite materials formed by embedding one or more reinforcing phases (such as ceramic particles, fibers, whiskers, etc.) into a metal or alloy matrix. This material combines the good electrical conductivity, thermal conductivity and plasticity of the metal matrix with the high strength, high modulus and wear resistance of the reinforcing phase, thereby achieving a significant improvement in performance. Depending on the matrix material, it can be divided into various types such as aluminum-based, magnesium-based, titanium-based, nickel-based, copper-based and high-temperature alloy-based. The selection of these matrix materials is mainly based on their respective physical and chemical properties, as well as the specific requirements of the application environment.
[0003] Metal matrix composites have attracted much attention due to their excellent performance and wide range of applications. In the aerospace field, metal matrix composites are used to manufacture lightweight and high-strength structural parts and engine components, such as aircraft landing gear, engine blades and turbine disks. The lightweight design of these components not only improves the fuel efficiency and performance of aircraft, but also reduces manufacturing and maintenance costs.
[0004] The main challenges in the preparation of metal matrix composites include interface bonding, cost control and processing difficulty. Interface bonding is one of the key factors affecting the performance of composite materials, and appropriate surface treatment and interface modification technology are needed to improve the interface bonding strength. In terms of cost control, the high cost of metal matrix composites due to the need to use high-cost raw materials and sophisticated equipment during the preparation process limits their widespread application.
[0005] In view of the above analysis, the technical problems that urgently need to be solved in the prior art are: low interface bonding strength and high cost. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a layered titanium-based composite material with alternating soft and hard layers and a preparation method thereof.
[0007] The present invention is achieved by a method for preparing a layered titanium-based composite material with alternating soft and hard layers, comprising the following steps:
[0008] Step 1: laser cleaning the surface of the TC4 titanium alloy substrate material to remove oxide film and impurities on the substrate surface;
[0009] Step 2: Using laser fuse technology in a pure argon atmosphere, TC4 soft layer cladding is performed on the surface of the cleaned TC4 titanium alloy substrate;
[0010] Step 3: Using laser nitridation technology to 2 -Ar mixed atmosphere, in-situ nitriding treatment is performed on the prepared TC4 soft layer to obtain a TiN hard layer of a certain thickness;
[0011] Step 4, repeating steps 2 and 3 to obtain a layered titanium-based composite material with alternating soft and hard layers.
[0012] Furthermore, in step 1, the laser power for laser cleaning is 200-1000 W, the scanning speed is 15-30 mm / s, and the spot diameter is 5 mm.
[0013] Furthermore, the TC4 titanium alloy matrix material is a TC4 solid welding wire with a diameter of 1 mm; the purity of the argon gas is 99.99%.
[0014] Furthermore, in step 2 and step 3, the laser power is: 1400-1700 W, the wire feeding speed is: 10-20 mm / s, the scanning speed is: 5-15 mm / s, the spot diameter is: 3 mm, the offset is: 1-3 mm, and the gas flow rate is: 30 L / min.
[0015] Furthermore, in step 3, a gas mixer is used to mix high-purity argon gas and nitrogen gas according to a preset gas flow ratio; N 2 The concentration is N 2 -2% to 20% of the Ar mixed gas.
[0016] Furthermore, in step three, the laser power is: 1300-2000 W, the scanning speed is: 5-15 mm / s, the spot diameter is: 3 mm, the offset is: 1-3 mm, and the gas flow rate is: 25 L / min.
[0017] Another object of the present invention is to provide a system for preparing a layered titanium-based composite material with alternating soft and hard layers for implementing the preparation method, comprising:
[0018] Laser cleaning unit, used to perform laser cleaning on the surface of TC4 titanium alloy substrate material to remove oxide film and impurities on the substrate surface;
[0019] A gas mixer, used to mix high-purity argon gas and nitrogen gas according to a preset gas flow ratio;
[0020] A laser fuse unit, configured with equipment for performing TC4 cladding on the surface of the cleaned TC4 titanium alloy substrate to obtain a TC4 soft layer;
[0021] Laser nitriding unit, used to prepare TiN hard layer by laser nitriding on TC4 titanium alloy cladding layer.
[0022] Furthermore, the laser cleaning unit is equipped with a controller for adjusting laser power and scanning speed to adapt to TC4 titanium alloy substrate materials of different thicknesses and types.
[0023] Furthermore, the gas mixer can automatically adjust the flow ratio of argon and nitrogen, and is equipped with a sensor for monitoring and adjusting the composition ratio of the mixed gas to ensure the stability and consistency of the mixed atmosphere during the laser nitriding process.
[0024] Another object of the present invention is to provide a method for preparing a layered titanium-based composite material with soft and hard layers, wherein the soft layer is TC4 alloy and the hard layer is a hard TiN ceramic phase.
[0025] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0026] First, the titanium-based composite material with a layered structure of the present invention can make the final composite material have the functions of high strength and lightweight, and at the same time has many advantages such as good high temperature resistance, strong heat resistance, good corrosion resistance, high mechanical strength, etc. It has a wide range of applications and can be used in aerospace, biomedicine, petrochemical, weapons and equipment, and other fields.
[0027] The technical solution of the present invention overcomes the problems of insufficient wear resistance and limited mechanical strength of titanium-based materials in the prior art by constructing a composite material with alternating soft and hard layers on the surface of titanium-based materials. In industrial applications, although traditional titanium alloys have an excellent strength-to-weight ratio, they have low wear resistance and are easily shortened in service life due to surface wear, especially in high-friction, high-load environments. The present invention utilizes laser cleaning, cladding, nitriding and other technologies to innovatively prepare a layered structure with alternating soft and hard layers on the surface of titanium alloys, so that the material has both high strength and wear resistance, achieving significant technological progress.
[0028] First, the present invention effectively improves the comprehensive mechanical properties of titanium alloy by introducing an alternating combination of TC4 soft layer and TiN hard layer. Traditional titanium-based materials only use a single hardened layer or overall coating to enhance wear resistance, but often sacrifice the toughness of the material. This technical solution improves wear resistance through the hard layer while maintaining the flexibility of the material, achieving a "strong and tough" balance and extending the service life of the material.
[0029] Secondly, the process significantly improves the processing efficiency of the material. Traditional composite coating methods such as electroplating and ion nitriding require a large number of processes and have poor interlayer bonding strength. The present invention uses laser technology for cladding and nitriding, which not only saves time, but also enhances the interlayer bonding quality, thereby improving the stability and reliability of the material. In addition, the technical solution avoids complex multi-layer processing procedures and effectively reduces production costs.
[0030] Finally, the present invention provides a better choice for wear-resistant titanium alloy materials in high-demand industrial fields such as aviation, aerospace, and automobiles, especially showing significant technological progress in high-friction and wear-resistant application environments. The structural innovation of this layered titanium-based composite material brings an efficient and low-cost production solution to the industry and significantly improves the performance and application range of the material.
[0031] Second, the technical solution of the present invention fills the technical gap in the industry at home and abroad: the present invention realizes the wire-level additive manufacturing of titanium nitride-titanium alloy layered composite materials for the first time, greatly improving production efficiency and reducing production costs.
[0032] The technical solution of the present invention solves the deficiencies of titanium-based composite materials in the prior art in terms of wear resistance, corrosion resistance and overall mechanical properties in industrial applications, and achieves significant technical progress in the following aspects:
[0033] 1. Improve the wear resistance and service life of materials
[0034] Although traditional titanium alloys have excellent light weight and corrosion resistance, they are not good at wear resistance, especially in applications that require long-term wear. The present invention constructs a hard TiN layer on the surface of the TC4 titanium alloy matrix to give the material higher surface hardness and wear resistance. The introduction of the TiN hard layer effectively improves the material's wear resistance and significantly extends the material's service life in a high wear environment.
[0035] 2. Enhance the impact toughness of the material
[0036] Existing hard coating technology often causes the surface of the material to become brittle and prone to cracking under impact loads. The present invention adopts a structure of alternating soft and hard layers in design. Through the composite structure of alternating TC4 soft layers and TiN hard layers, the material has both high hardness and good toughness. The high ductility of the TC4 soft layer can buffer external impacts, thereby preventing the material from surface cracking under high stress conditions and improving the impact resistance of the material.
[0037] 3. Improve the corrosion resistance of materials
[0038] Titanium alloys have good corrosion resistance in oxidizing environments, but their corrosion resistance still needs to be enhanced in specific applications. Due to its high chemical stability, the TiN hard layer can form an effective protective barrier in a corrosive environment to prevent corrosive media from invading the interior of the matrix. The multi-layer structure design enables the material to exhibit excellent corrosion resistance in a corrosive environment, expanding its application range in harsh environments.
[0039] 4. Reduce residual stress in heat affected zone
[0040] In the surface coating process of traditional titanium-based materials, the heat treatment process often introduces large residual stress, which makes the material prone to warping or peeling during use. The present invention uses advanced processes such as laser cleaning, laser cladding and in-situ nitriding to effectively control the temperature and stress distribution in the heat-affected zone and reduce the generation of residual stress. This solution ensures the stable combination of the soft and hard layer interfaces, significantly improving the reliability and durability of the material.
[0041] Through the above technological advances, the present invention effectively solves the shortcomings of traditional titanium-based composite materials in application, and is suitable for fields such as aerospace, marine engineering and high-precision equipment that require both high strength and wear resistance, and promotes the widespread application of titanium-based composite materials in various industrial fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 It is a flow chart of a method for preparing a layered titanium-based composite material with alternating soft and hard layers provided by an embodiment of the present invention;
[0043] Figure 2 is a macroscopic morphology diagram of a layered titanium-based composite material provided by an embodiment of the present invention;
[0044] Figure 3 is a cross-sectional optical micrograph of a layered titanium-based composite material provided by an embodiment of the present invention;
[0045] Figure 4 This is a cross-sectional SEM image of the layered titanium-based composite material provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0047] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a layered titanium-based composite material with alternating soft and hard layers, comprising the following steps:
[0048] Step 1: laser cleaning the surface of the TC4 titanium alloy substrate material to remove oxide film and impurities on the substrate surface;
[0049] Step 2: Using laser fuse technology in a pure argon atmosphere, TC4 soft layer cladding is performed on the surface of the cleaned TC4 titanium alloy substrate;
[0050] Step 3: Using laser nitridation technology to 2 -Ar mixed atmosphere, in-situ nitriding treatment is performed on the prepared TC4 soft layer to obtain a TiN hard layer of a certain thickness;
[0051] Step 4, repeating steps 2 and 3 to obtain a layered titanium-based composite material with alternating soft and hard layers.
[0052] The method for preparing a layered titanium-based composite material with alternating soft and hard layers provided in an embodiment of the present invention aims to improve the wear resistance, corrosion resistance and mechanical properties of the titanium-based composite material through precise multilayer structure design.
[0053] Its main working principles include the following four aspects:
[0054] 1. Surface pretreatment of substrate material
[0055] The surface of the TC4 titanium alloy substrate is treated by laser cleaning technology to remove the oxide film and surface impurities, thereby increasing the cleanliness of the substrate surface. This cleaning technology uses the high energy instantaneous effect of the laser to remove the surface layer, so that the surface of the substrate material reaches a good activation state, which is conducive to the firm bonding of subsequent layers and significantly improves the interface bonding strength.
[0056] 2. Cladding technology of soft layer
[0057] In a pure argon protection environment, the TC4 titanium alloy material is clad on the substrate surface using laser fuse technology to form a soft layer. While accurately controlling the thickness and organizational structure of the cladding layer, the laser fuse technology can effectively reduce the residual stress in the heat-affected zone and maintain a high material plasticity. The TC4 soft layer has good ductility and toughness, can provide the material with high impact toughness, and provide an ideal matrix for the next hard layer construction.
[0058] 3. In-situ nitriding treatment of hard layer
[0059] In a mixed atmosphere of nitrogen and argon, the prepared TC4 soft layer is in-situ nitrided using laser nitriding technology to form a TiN hard layer on the surface. The hard layer is mainly composed of TiN phase and has high hardness, excellent wear resistance and chemical stability. The in-situ nitriding treatment allows nitrogen to diffuse into the titanium matrix and react with titanium to form a hard nitride layer, which improves the surface strength and hardness of the composite material.
[0060] 4. Multi-layer structure construction of soft and hard layers
[0061] By repeating the steps of soft layer cladding and hard layer nitriding, an alternating soft and hard layer composite structure is formed. The toughness of the soft layer and the wear resistance of the hard layer complement each other, making the material have better impact resistance, corrosion resistance and fatigue resistance. This layered structure of alternating soft and hard layers not only improves the comprehensive mechanical properties of the material, but also effectively disperses and absorbs external impacts, extending the service life of the material.
[0062] The method for preparing a layered titanium-based composite material with alternating soft and hard layers provided in an embodiment of the present invention aims to alternately form soft layers and hard layers on a titanium alloy substrate by laser technology to enhance the comprehensive mechanical properties of the material.
[0063] Here is how it works in detail:
[0064] 1. Laser cleaning of substrate surface
[0065] During the preparation process, the surface of the titanium alloy (TC4) substrate is first laser cleaned. This step uses a high-energy laser beam to act on the substrate surface to remove the oxide film and impurities on the substrate surface, leaving the surface in a clean state. A clean surface can improve the adhesion of subsequent cladding materials and ensure the interface quality and bonding strength between the composite layers.
[0066] 2. Soft layer cladding
[0067] After cleaning, a layer of TC4 titanium alloy is melted on the substrate surface to form a soft layer using laser fuse technology under the protection of pure argon atmosphere. This soft layer acts as a buffer to enhance the ductility and impact resistance of the material. Laser fuse technology acts on the substrate through local high temperature, so that the titanium alloy material is quickly melted and cooled under the action of laser, ensuring that the soft layer structure is uniform and dense, and firmly bonded to the substrate material.
[0068] 3. Hard layer nitriding
[0069] After the soft layer is prepared, laser nitridation technology is used to 2 -Ar mixed atmosphere in situ nitriding treatment of TC4 soft layer to generate a TiN hard layer with a certain thickness. During laser nitriding, under laser heating, nitrogen penetrates into the surface of titanium alloy and combines with titanium to generate a TiN hard layer. The TiN hard layer has high hardness and wear resistance, making the composite material show stronger wear resistance in high friction and wear environment.
[0070] 4. Alternate molding of soft and hard layers
[0071] After forming the first pair of soft and hard layers, the cladding and nitriding steps are repeated to continue to stack the alternating structure of soft and hard layers, gradually building a multi-layer composite material. The alternating soft and hard layer structure gives the material excellent composite properties: the hard layer provides wear protection, while the soft layer improves the material's toughness and impact resistance. The number of layers can be adjusted according to the required performance requirements, and multifunctionality is achieved by optimizing the structure.
[0072] 5. Argon and nitrogen atmosphere control
[0073] In the process of forming soft and hard layers, it is very important to control the atmosphere of argon and nitrogen. Pure argon atmosphere prevents oxidation of TC4 titanium alloy during the cladding process, while nitrogen-argon mixed atmosphere ensures sufficient penetration of nitrogen during the nitriding process, generating high-quality TiN hard layers, ensuring that each soft and hard layer is uniform and dense, so that the material achieves ideal mechanical properties.
[0074] 6.Performance optimization and final molding
[0075] After the cladding and nitriding treatment of all layers are completed, a layered titanium-based composite material with an alternating structure of soft and hard layers is obtained. The alternating configuration of soft and hard layers gives the material both the toughness of titanium alloy and the high hardness of TiN layer. This layered structure gives the material excellent wear resistance, impact resistance and fatigue resistance, making it suitable for high stress and wear resistance applications.
[0076] The TC4 titanium alloy has the advantages of high strength, low density, good corrosion resistance and biocompatibility. The TiN is a very hard ceramic phase with the advantages of high hardness, high melting point, high chemical stability, excellent thermal conductivity, good biocompatibility, etc. The layered titanium-based composite material has the advantages of high strength, good wear resistance, high temperature resistance, good biocompatibility, etc.
[0077] Furthermore, in step 1, the laser power for laser cleaning is 200-1000 W, the scanning speed is 15-30 mm / s, and the spot diameter is 5 mm.
[0078] Furthermore, the TC4 titanium alloy matrix material is a TC4 solid welding wire with a diameter of 1 mm; the purity of the argon gas is 99.99%.
[0079] Furthermore, in step 2 and step 3, the laser power is: 1400-1700 W, the wire feeding speed is: 10-20 mm / s, the scanning speed is: 5-15 mm / s, the spot diameter is: 3 mm, the offset is: 1-3 mm, and the gas flow rate is: 30 L / min.
[0080] Furthermore, in step 3, a gas mixer is used to mix high-purity argon gas and nitrogen gas according to a preset gas flow ratio; N 2 The concentration is N 2-2% to 20% of the Ar mixed gas.
[0081] Furthermore, in step three, the laser power is: 1300-2000 W, the scanning speed is: 5-15 mm / s, the spot diameter is: 3 mm, the offset is: 1-3 mm, and the gas flow rate is: 25 L / min.
[0082] The embodiment of the present invention provides a system for preparing a layered titanium-based composite material with alternating soft and hard layers for implementing the preparation method, comprising:
[0083] Laser cleaning unit, used to perform laser cleaning on the surface of TC4 titanium alloy substrate material to remove oxide film and impurities on the substrate surface;
[0084] A gas mixer, used to mix high-purity argon gas and nitrogen gas according to a preset gas flow ratio;
[0085] A laser fuse unit, configured with equipment for performing TC4 cladding on the surface of the cleaned TC4 titanium alloy substrate to obtain a TC4 soft layer;
[0086] Laser nitriding unit, used to prepare TiN soft layer by laser nitriding on TC4 titanium alloy cladding layer.
[0087] Furthermore, the laser cleaning unit is equipped with a controller for adjusting laser power and scanning speed to adapt to TC4 titanium alloy substrate materials of different thicknesses and types.
[0088] Furthermore, the gas mixer can automatically adjust the flow ratio of argon and nitrogen, and is equipped with a sensor for monitoring and adjusting the composition ratio of the mixed gas to ensure the stability and consistency of the mixed atmosphere during the laser nitriding process.
[0089] The layered titanium-based composite material with alternating soft and hard layers of the present invention has wide applications in military equipment. The hard TiN layer of the material significantly improves the hardness and wear resistance of the surface, enabling it to exhibit excellent resistance in high-impact environments, and is therefore particularly suitable for key components such as missiles, rockets, and armored vehicles. Its structural design effectively improves the impact resistance of the components, and can maintain high reliability and extend service life under harsh military conditions.
[0090] In aviation and gas turbine applications, this titanium-based composite material also shows significant technical advantages. Aircraft engine blades and gas turbine components are in high-temperature, high-speed airflow environments for a long time, and are prone to oxidation and corrosion. The TiN hard layer in the present invention provides reliable anti-oxidation protection, and the soft layer of TC4 alloy increases toughness and ductility, thereby effectively improving the overall durability and corrosion resistance, ensuring stable operation of the equipment in harsh working environments.
[0091] In the medical field, especially in dentistry and orthopedics, titanium nitride composites have become an ideal choice for implant materials due to their excellent biocompatibility and wear resistance. The titanium nitride surface has excellent antibacterial properties, which can reduce the risk of infection and inflammation, thereby improving the long-term stability of the implant and the comfort of the patient. This feature makes it particularly suitable for medical devices such as artificial joints and dental implants that have extremely high requirements for biocompatibility and durability.
[0092] In summary, the layered titanium-based composite material provided by the present invention can be widely used in military, aviation, medical and other fields due to its excellent wear resistance, impact resistance and corrosion resistance, greatly improving the service life and reliability of related products and promoting the technological progress of high-performance composite materials in various industries.
[0093] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modification, equivalent substitution and improvement made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a layered titanium-based composite material with alternating soft and hard layers, characterized in that: The following steps are involved: Step 1: laser cleaning the surface of the TC4 titanium alloy substrate material to remove oxide film and impurities on the substrate surface; Step 2: Using laser fuse technology in a pure argon atmosphere, TC4 soft layer cladding is performed on the surface of the cleaned TC4 titanium alloy substrate; Step 3: Using laser nitridation technology, in-situ nitriding treatment is performed on the prepared TC4 soft layer in a N2-Ar mixed atmosphere to obtain a TiN hard layer of a certain thickness; Step 4, repeating steps 2 and 3 to obtain a layered titanium-based composite material with alternating soft and hard layers.
2. The method for preparing a layered titanium-based composite material with alternating soft and hard layers according to claim 1, characterized in that: The laser power for laser cleaning in step 1 is: 200-1000 W, the scanning speed is: 15-30 mm / s, and the spot diameter is: 5 mm.
3. The method for preparing a layered titanium-based composite material with alternating soft and hard layers according to claim 1, characterized in that: The TC4 titanium alloy matrix material is a TC4 solid welding wire with a diameter of 1 mm; the purity of the argon gas is 99.99%.
4. The method for preparing a layered titanium-based composite material with alternating soft and hard layers according to claim 1, characterized in that: In the step 2 and step 3, the laser power is: 1400-1700W, the wire feeding speed is: 10-20mm / s, the scanning speed is: 5-15mm / s, the spot diameter is: 3mm, the offset is: 1-3mm, and the gas flow rate is: 30L / min.
5. The method for preparing a layered titanium-based composite material having alternating soft and hard layers according to claim 1, characterized in that: In the step three, a gas mixer is used to mix high-purity argon gas and nitrogen gas according to a preset gas flow ratio; the N2 concentration is 2% to 20% of the N2-Ar mixed gas.
6. The method for preparing a layered titanium-based composite material having alternating soft and hard layers according to claim 1, characterized in that: In the step three, the laser power is 1300-2000 W, the scanning speed is 5-15 mm / s, the spot diameter is 3 mm, the offset is 1-3 mm, and the gas flow rate is 25 L / min.
7. A system for preparing a layered titanium-based composite material having soft and hard layers alternating therebetween for implementing the preparation method according to any one of claims 1 to 6, characterized in that: include: Laser cleaning unit, used to perform laser cleaning on the surface of TC4 titanium alloy substrate material to remove oxide film and impurities on the substrate surface; A gas mixer, used to mix high-purity argon gas and nitrogen gas according to a preset gas flow ratio; A laser fuse unit, configured with equipment for performing TC4 cladding on the surface of the cleaned TC4 titanium alloy substrate to obtain a TC4 soft layer; Laser nitriding unit, used to prepare TiN hard layer by laser nitriding on TC4 titanium alloy cladding layer.
8. The system for preparing a layered titanium-based composite material with alternating soft and hard layers as claimed in claim 7, characterized in that: The laser cleaning unit is equipped with a controller for adjusting laser power and scanning speed, and is adaptable to TC4 titanium alloy substrate materials of different thicknesses and types.
9. The system for preparing a layered titanium-based composite material having alternating soft and hard layers as claimed in claim 7, characterized in that: The gas mixer can automatically adjust the flow ratio of argon and nitrogen, and is equipped with a sensor for monitoring and adjusting the composition ratio of the mixed gas to ensure the stability and consistency of the mixed atmosphere during the laser nitriding process.
10. A titanium-based composite material with alternating soft and hard layers prepared by the method for preparing a titanium-based composite material with alternating soft and hard layers as claimed in any one of claims 1 to 6, characterized in that: The soft layer is TC4 alloy, and the hard layer is hard TiN ceramic phase.
Citation Information
Patent Citations
Metal-metal nitride laminated coating resistant to high temperature marine environment corrosion and preparation method thereof
CN110158035A
In-situ preparation method and system of reinforced erosion-resistant TC4-TiN composite material
CN117660956A
Treatment process for improving mechanical and fatigue properties of TC4 titanium alloy metal rubber
CN118835187A
Cutting tool made of surface coated cubic boron nitride-base very high pressure sintered material
JP2008302439A